Most Ancient Verse. Selected and Translated by Th. Jacobsen and John A. Wilson. With an Introduction by David Green - Jacobsen, Thorkild (1963)
p. 2-29: Sumerian Verse: The Kishkanu of White Magic; Girl under the Moon; Bucolic; The Sister as Matchmaker; Love Song to Kling Shu-Suen; The Bride Sings; Deadly Diseases; You Were Too Young to Die; The Wild Bull, Who Has Lain Down; My Heart Plays a Reedpipe; The Dead Son to his Mother.